The transcriptional mediator component Med12 is required for hindbrain boundary formation. - Sung-Kook Hong; Igor B Dawid (PLoS ONE, 2011)
Background Rhombomere boundaries form during hindbrain segmentation and are critical for maintaining segmental integrity and regulating migration in the hindbrain. Some genetic models affecting hindbrain boundary formation have been described, but involvement of components of the transcriptional mediator complex in boundary formation has not reported so far. Principal findings The kto/med12 mutant zebrafish, which affects the Mediator component Med12, causes specific loss of rhombomere boundary cells even though segmentation of the hindbrain takes place at least in part. In kto mutant embryos, cells forming rhombomere boundaries were largely absent as indicated by the use of several marker genes. While no obvious increase in cell death was observed, we found a notable reduction of cell proliferation in the hindbrain of kto mutant zebrafish. Conclusions The kto/med12 mutation results in specific defects of boundary cell formation in the zebrafish hindbrain.